AIAA Scitech 2019 Forum 2019
DOI: 10.2514/6.2019-0463
|View full text |Cite
|
Sign up to set email alerts
|

On the arc transition mechanism in nanosecond air discharges

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 24 publications
(30 reference statements)
8
31
0
Order By: Relevance
“…The authors [33] remark that the nature of the observed electron cloud is still under discussion and mention the field emission in strong electric field and a possibility of production of a supercritical fluid during explosive heating of a single spike or multiple spikes on the cathode. Non-numerous experimental observations [11,13,14,37] obtained in mm or sub-mm pin-to-pin gaps report the start of the filament from the cathode, then, with a delay of the order of 1 ns -from the anode, and then the filaments merge in the middle of the gap [13,37]. Significant decrease of the streamer radius, by a factor of 3 − 5, on the time scale 0.5 ns before the filamentation is recently reported [13].…”
Section: Near-electrode Processes and Filament Propagation As An Ionimentioning
confidence: 99%
See 2 more Smart Citations
“…The authors [33] remark that the nature of the observed electron cloud is still under discussion and mention the field emission in strong electric field and a possibility of production of a supercritical fluid during explosive heating of a single spike or multiple spikes on the cathode. Non-numerous experimental observations [11,13,14,37] obtained in mm or sub-mm pin-to-pin gaps report the start of the filament from the cathode, then, with a delay of the order of 1 ns -from the anode, and then the filaments merge in the middle of the gap [13,37]. Significant decrease of the streamer radius, by a factor of 3 − 5, on the time scale 0.5 ns before the filamentation is recently reported [13].…”
Section: Near-electrode Processes and Filament Propagation As An Ionimentioning
confidence: 99%
“…Non-numerous experimental observations [11,13,14,37] obtained in mm or sub-mm pin-to-pin gaps report the start of the filament from the cathode, then, with a delay of the order of 1 ns -from the anode, and then the filaments merge in the middle of the gap [13,37]. Significant decrease of the streamer radius, by a factor of 3 − 5, on the time scale 0.5 ns before the filamentation is recently reported [13]. Significant changes of parameters of the streamer plasma in the radial direction before the filamentation were observed in [14]: significant increase of gas temperature in the middle of the channel was measured; significant, 5-6 times, decrease of radius was reported.…”
Section: Near-electrode Processes and Filament Propagation As An Ionimentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism explains in our opinion the fast transition (< 1 ns) from a non-equilibrium to a thermal plasma as experimentally observed with nanosecond discharges in Refs. [17,21,43]. Ionization rates of N2(X, A, B, C, a').…”
Section: Resultsmentioning
confidence: 99%
“…Stark broadening was also used for electron number density measurement in several works in pin-to-pin or pinto-plane configuration [16][17][18][19] and all authors reported electron number densities higher than 10 18 cm -3 . Such a high electron number density was also reported in SDBD discharges [20][21][22].…”
Section: Introductionmentioning
confidence: 99%